Analysis of deforestation in the Matahuayo-Tahuayo sector (Loreto) using images from TM, ETM+ and OLI sensors during the period 2007-2015 - Choccña, Michel (2023)
This project presents a methodology to identify deforestation in the Matahuayo sector. Tahuayo, which arises from the problem of the expansion of deforestation in tropical forests from Peru. The main objective of this study is to implement a methodology that allows detecting and quantify the deforested areas in the aforementioned sector, located in the department of Loreto. 36 Landsat 5, 7 and 8 L1T level image data were used for the time 2007 - 2015 with spatial resolution of 30 m x 30 m. The implemented methodology consists of three phases: (i) The preprocessing stage, the radiometric correction was developed, the TOA reflectance was calculated and atmospheric correction to obtain the reflectance of the ground surface. (ii) In processing Spatial and temporal distribution maps were produced from different biophysical indices (NDVI, RVI) and transformations (Tasseled Cap, PCA) that constitute the compound of 18 synthetic bands and Through spectral separability we select the synthetic bands that are used as inputs in unsupervised K-means classification. (iii) In the post processing the contours were generated of deforested areas for each year of study. From the results obtained it can be indicate a reduction of extensive areas of Amazonian forests in the study sector for the period 2007-2015. Deforestation obtained in hectares per year presents a linear upward trend of 9635 ha/year.